Glutamyl-Prolyl-tRNA Synthetase Regulates Proline-Rich Pro-Fibrotic Protein Synthesis During Cardiac Fibrosis. Issue 6 (28th August 2020) - Wu, Jiangbin; Subbaiah, Kadiam C. Venkata; Xie, Li Huitong; Jiang, Feng; Khor, Eng-Soon; Mickelsen, Deanne; Myers, Jason R.; Tang, Wai Hong Wilson; Yao, Peng
Abstract : Rationale: Increased protein synthesis of profibrotic genes is a common feature in cardiac fibrosis and heart failure. Despite this observation, critical factors and molecular mechanisms for translational control of profibrotic genes during cardiac fibrosis remain unclear. Objective: To investigate the role of a bifunctional ARS (aminoacyl-tRNA synthetase), EPRS (glutamyl-prolyl-tRNA synthetase) in translational control of cardiac fibrosis. Methods and Results: Results from reanalyses of multiple publicly available data sets of human and mouse heart failure, demonstrated that EPRS acted as an integrated node among the ARSs in various cardiac pathogenic processes. We confirmed that EPRS was induced at mRNA and protein levels (≈1.5–2.5-fold increase) in failing hearts compared with nonfailing hearts using our cohort of human and mouse heart samples. Genetic knockout of one allele of Eprs globally ( Eprs +/− ) using CRISPR-Cas9 technology or in a Postn-Cre-dependent manner ( Eprs flox/+ ; Postn MCM/+ ) strongly reduces cardiac fibrosis (≈50% reduction) in isoproterenol-, transverse aortic constriction-, and myocardial infarction (MI)-induced heart failure mouse models. Inhibition of EPRS using a PRS (prolyl-tRNA synthetase)-specific inhibitor, halofuginone, significantly decreases translation efficiency (TE) of proline-rich collagens in cardiac fibroblasts as well as TGF-β (transforming growth factor-β)-activated myofibroblasts. Overexpression of EPRS increases collagen protein expression in primary cardiac fibroblasts under TGF-β stimulation. Using transcriptome-wide RNA-Seq and polysome profiling-Seq in halofuginone-treated fibroblasts, we identified multiple novel Pro-rich genes in addition to collagens, such as Ltbp2 (latent TGF-β-binding protein 2) and Sulf1 (sulfatase 1), which are translationally regulated by EPRS. SULF1 is highly enriched in human and mouse myofibroblasts. In the primary cardiac fibroblast culture system, siRNA-mediated knockdown of SULF1 attenuates cardiac myofibroblast activation and collagen deposition. Overexpression of SULF1 promotes TGF-β-induced myofibroblast activation and partially antagonizes anti-fibrotic effects of halofuginone treatment. Conclusions: Our results indicate that EPRS preferentially controls translational activation of proline codon rich profibrotic genes in cardiac fibroblasts and augments pathological cardiac remodeling. Abstract : Supplemental Digital Content is available in the text.